Mindfulness and impulsive behavior: exploring the mediating roles of self-reflection and coping effectiveness among high-level athletes in Central China - Liang, Peili; Jiang, Hongyu; Wang, Huilin; Tang, Jiaxin (Frontiers in Psychology, 2024)
In the highly competitive field of sports, impulsive behavior by athletes not only threatens personal and team harmony but also poses significant risks to their careers and public image. Despite these behaviors often becoming the focus of public attention, their underlying causes and prevention strategies remain relatively unknown. This study delves deep into the impact of mindfulness on athletes' impulsive behavior, revealing the mediating roles of self-reflection and coping effectiveness.Methods: Using a combination of snowball and convenience sampling, a sample of 403 athletes from high-level sports teams in the Central China region participated in a questionnaire survey. The data were analyzed using Amos v.23 software.The findings indicate a positive correlation between mindfulness and coping effectiveness (standardized coefficient = 0.336, p < 0.001), as well as between self-reflection and coping effectiveness (standardized coefficient = 0.406, p < 0.001). There is a negative correlation between coping effectiveness and impulsive behavior (standardized coefficient = -0.476, p < 0.001). The positive impact of mindfulness on impulsive behavior (standardized coefficient = -0.371, p < 0.01) is mediated by self-reflection and coping effectiveness. The explanatory power of this study is R² = 0.35. Discussion: Mindfulness reduces impulsive behavior by enhancing self-reflection capabilities and improving coping effectiveness. Based on these substantive research results, to mitigate impulsive behavior in athletes, it is recommended that the National Sports Administration and coaches actively implement mindfulness training. Additionally, targeted psychological intervention strategies should be developed to enhance athletes' mental health levels and optimize their sports performance.